Pengaruh pengetahuan, risiko, promosi terhadap minat berinvestasi reksa dana bagi GENERASI Z - Khairunnisa', Tasya; Bahrun Ni’am, Zaki (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2023)
This study is to determine the effect of knowledge, risk, and promotion on investment interest for Generation Z. The independent variables used in this study are knowledge, risk and promotion. While the dependent variable in this study is interest in investing. The research was conducted using quantitative methods. The population in this test is Sharia Financial Management students of UIN Sayyid Ali Rahmatullah Tulungagung in 2020-2021. The sampling method used purposive sampling method and questionnaires were used to collect data. The sample size was 326 respondents. The data were analyzed with descriptive statistics, validity test, normality test, classical assumption test, multiple linear regression analysis test, hypothesis testing and coefficient of determination (R2) test using the SPSS version 25 application. The results of this study indicate a simultaneous relationship between knowledge, risk and promotion of mutual fund investment interest for generation Z. While partially the knowledge variable has a significant effect on mutual fund investment interest, the risk variable has no significant effect on mutual fund investment interest and the promotion variable has a significant effect on mutual fund investment interest.